Is Siwak (Chewing Stick) an Effective Oral Hygiene Practice in Modern Society? - Tuti Ningseh Mohd Dom; Shahida Mohd Said; Ahmad Munawar Ismail; Haslinda Ramli (UKM Press, 2024)
Indexed by WOS/Scopus/ERA/MyCite